Pengaruh Dana Program Beasiswa Bidimisi Terhadap Prestasi Belajar Mahasiswa Jurusan Pendidikan Ekonomi Angkatan 2018 Universitas Negeri Gorontalo - Iswan Ali; Radia Hafid; Melizubaida Mahmud; Meyko Panigoro; Sudirman (Jurnal Pendidikan Ekonomi dan Bisnis, 2025)
The objective of this present Research was to determine to what extent the effect of the bidikmisi scholarship program funds on students’ learning achievement at the Departement of Economics Education, Universitas Negeri Gorontalo, Class of 2018. This Research employed a quantitative approach using aquantitative correlaional method with a sampel of 81 students. At the same time, the data collection techniques used in this Research Wet observation, interviews, questionnairess, and documentation, while the data analysis technique was simple linear regression. The Research dinding based on hypothesis testing indicated that the Bidikmisi scholarsip had a positive effect on students’ learning achievement at the Departement of Economics Education with a correlation coefficient value indicating a low level of correlation and the value of the coefficient of determination indicating the percentage level of the effect of the Bidikmisi scholarsip variable on students’ learning achievement of 13,7%.